An Update on Pharmacologic Management of Neonatal Hypotension: When, Why, and Which Medication - Eleni Agakidou; Ilias Chatziioannidis; Angeliki Kontou; Theodora Stathopoulou; William Chotas; Kosmas Sarafidis (MDPI AG, 2024)
Anti-hypotensive treatment, which includes dopamine, dobutamine, epinephrine, norepinephrine, milrinone, vasopressin, terlipressin, levosimendan, and glucocorticoids, is a long-established intervention in neonates with arterial hypotension (AH). However, there are still gaps in knowledge and issues that need clarification. The main questions and challenges that neonatologists face relate to the reference ranges of arterial blood pressure in presumably healthy neonates in relation to gestational and postnatal age; the arterial blood pressure level that potentially affects perfusion of critical organs; the incorporation of targeted echocardiography and near-infrared spectroscopy for assessing heart function and cerebral perfusion in clinical practice; the indication, timing, and choice of medication for each individual patient; the limited randomized clinical trials in neonates with sometimes conflicting results; and the sparse data regarding the potential effect of early hypotension or anti-hypotensive medications on long-term neurodevelopment. In this review, after a short review of AH definitions used in neonates and existing data on pathophysiology of AH, we discuss currently available data on pharmacokinetic and hemodynamic effects, as well as the effectiveness and safety of anti-hypotensive medications in neonates. In addition, data on the comparisons between anti-hypotensive medications and current suggestions for the main indications of each medication are discussed.